2020
DOI: 10.1101/2020.05.03.20089813
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Personalized Predictive Models for Symptomatic COVID-19 Patients Using Basic Preconditions:Hospitalizations, Mortality, and the Need for an ICU or Ventilator

Abstract: Background: The rapid global spread of the virus SARS-CoV-2 has provoked a spike in demand for hospital care. Hospital systems across the world have been over-extended, including in Northern Italy, Ecuador, and New York City, and many other systems face similar challenges. As a result, decisions on how to best allocate very limited medical resources have come to the forefront. Specifically, under consideration are decisions on who to test, who to admit into hospitals, who to treat in an Intensive Care Unit (IC… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 20 publications
2
24
0
Order By: Relevance
“…In our hospital, there was a significant increase in the number of patients with AKI of all stages in the COVID‐19 positive population when compared to the same time period in 2019. The rate of AKI in the COVID‐19 positive population is comparable to other studies 8,22,23 although the incidence of AKI in European and North American studies appears to be greater than those conducted in China 6 . Patients also suffered similarly poor outcomes such as admission to ICU for organ support, increased length of stay and death.…”
Section: Discussionsupporting
confidence: 58%
“…In our hospital, there was a significant increase in the number of patients with AKI of all stages in the COVID‐19 positive population when compared to the same time period in 2019. The rate of AKI in the COVID‐19 positive population is comparable to other studies 8,22,23 although the incidence of AKI in European and North American studies appears to be greater than those conducted in China 6 . Patients also suffered similarly poor outcomes such as admission to ICU for organ support, increased length of stay and death.…”
Section: Discussionsupporting
confidence: 58%
“…We identified 19 studies that examined the relationship and included them in this analysis 1,28,38,40,44,47–58 . Table S4 presents the results 1,45,47,48,59,60 ; all showed a significantly higher prevalence of individuals with obesity among hospitalized patients than among patients not hospitalized or the general population. The pooled OR was 2.13 (95% CI, 1.74–2.60; p < 0.0001) (Figure 4).…”
Section: Epidemiological Relationships: Individuals With Overweight Amentioning
confidence: 99%
“…After screening, 27 articles were included for further analysis. 20 46 The process of selection of the included studies is shown in Figure 1 .…”
Section: Resultsmentioning
confidence: 99%
“…In our meta-analysis, information on the critical or severe condition was available in 11 studies. 23 , 35 44 Of the 21,387 patients with COVID-19 infection, 5411 patients suffered from critically ill condition during the study period: 507 patients in the CKD group and 4904 patients in the non-CKD group. The heterogeneity test showed high heterogeneity among these studies ( I 2 = 90%), and a random-effects model was used.…”
Section: Resultsmentioning
confidence: 99%